EFL Students’ Speaking Motivation in Speaking for Informal Interaction Class at English Department UNP - Vivit Tania Agnes; Leni Marlina (Universitas Negeri Padang, 2021)
This study aims to determine the level of speaking motivation of EFL students. The sample of this study consisted of 31 students who had participated in the Speaking Informal Interaction class in the English Department of UNP in the 2019 academic year. This research was a survey by distributing questionnaires and the results of the questionnaire were analyzed quantitatively and descriptively. Students were given a questionnaire to find out their level of speaking motivation. The questionnaire used is the Attitude / Motivation Test Battery (AMTB). The results of this study indicate that in grades K5-19 in the course Speaking for Informal Interaction they have a high level of speaking motivation and few of them have a moderate level. None of them are at a low level of motivation. It can be concluded that this class has very high speaking motivation.